Dampak Media Sosial terhadap Voting Behavior pada Gen Z - Mirzi Hayati; Aflah Zakinov Irta; Friskha Hapsari; Shefriana Putri Pulungan; Arriana Puspita Sari (CV. ITTC INDONESIA, 2026)
Social media is now one of the main sources of political information, especially for Gen Z, who were raised in a digital era. This study aims to explore how social media influences the voting behavior of Gen Z. The method used is a literature review by analyzing 19 journal articles published between 2019 and 2025. The results show that social media has a strong impact on increasing Gen Z's political interest and participation, as they are more active in seeking information and engaging in online political discussions. However, social media can also have negative effects, such as the spread of misinformation and political polarization caused by algorithm-based content. In addition to social media, other factors like cultural background, education, and group identity also influence Gen Z’s voting decisions. Therefore, it is important for Gen Z to have good digital and political literacy so they can filter information wisely and participate responsibly in democratic processes.